2005
DOI: 10.1379/csc-129r.1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the pentapeptide constituting a dominant epitope common to all eukaryotic heat shock protein 90 molecular chaperones

Abstract: We previously reported that, in human heat shock protein (Hsp) 90 (hHsp90), there are 4 highly immunogenic sites, designated sites Ia, Ib, Ic, and II. This study was performed to further characterize their epitopes and to identify the epitope that is potentially common to all members of the Hsp90 family. Panning of a bacterial library carrying randomized dodecapeptides revealed that Glu 251 -Ser-X-Asp 254 constituted site Ia and Pro 295 -Ile-Trp-Thr-Arg 299 , site Ic. Site II (Asp 701 -Pro 717 ) was composed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Mutant yeast cells with a disrupted HSC82 or HSP82 gene harboring pRS425‐GAL1‐core were cultured with (+) or without (−) 3% galactose for 72 h (A) or 2 h (C–E) at 30 °C. We used a monoclonal antibody that reacts with the Ic epitope common to Hsc82 and Hsp82 [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant yeast cells with a disrupted HSC82 or HSP82 gene harboring pRS425‐GAL1‐core were cultured with (+) or without (−) 3% galactose for 72 h (A) or 2 h (C–E) at 30 °C. We used a monoclonal antibody that reacts with the Ic epitope common to Hsc82 and Hsp82 [14].…”
Section: Resultsmentioning
confidence: 99%
“…We examined the Core by western blotting as described previously [12] and in the Supplemental Information. We used primary antibodies specific for actin (sc‐1616; Santa Cruz Biotechnology, Santa Cruz, CA, USA), Hsp90 (K41110, from Dr. Nemoto) [13,14], and Core (515S) [15].…”
Section: Methodsmentioning
confidence: 99%
“…Hsp90 protein contains three well-defined domains: N-, middle, and C-terminal (Buchner, 1999 ; Krishna and Gloor, 2001 ; Kishimoto et al, 2005 ; Kumar et al, 2007 ; Kadota and Shirasu, 2012 ). The N-terminal domain of Hsp90 is the most conserved among the studied species (Johnson, 2012 ), and additional studies using the N-terminal domain of eukaryotic gp96 demonstrated that this domain has immunomodulatory activity and that residues 34–222 are sufficient to retain the bound peptide (Gidalevitz et al, 2004 ).…”
Section: Hsp90 As Adjuvants In the Design Of Vaccines Against Infectimentioning
confidence: 99%
“…Several variations of this approach exist, utilizing a variety of display libraries, such as phage display, [ 7–9 ] yeast display, [ 10,11 ] and bacterial display. [ 12–16 ] Bacterial display systems, typically created in Escherichia coli (E. coli) , have been extensively utilized due to the relative ease of manipulation, rapid growth rate, and direct cell surface peptide expression characteristics. In contrast to phage display, the genetic material is passed on directly to the next sorting round during cell regrowth, rather than requiring reinfection of bacterial cells.…”
Section: Introductionmentioning
confidence: 99%